Spring and autumn stopover resources and land use patterns for the Rocky Mountain population of sandhill cranes in the San Luis Valley, Colorado - Vanausdall, Rachel Ann, author; Kendall, William L., advisor; Collins, Daniel P., committee member; Koons, David N., committee member; Sueltenfuss, Jeremy, committee member (Colorado State University. Libraries, 2024)
Stopover areas are important to migrant birds for resting and refueling on long journeys to and from their breeding grounds. Many birds use spring stopover areas to obtain adequate energy reserves to aid in reproduction, and the quality of habitat used during both spring and autumn migration can have cross-seasonal effects on vital rates, such as survival probability, later in the annual cycle. The Rocky Mountain Population of greater sandhill cranes (Antigone canadensis tabida) is a migrant population that stages in several western regions during the migratory period, but most of their time is spent on a single stopover area during the autumn and spring. While this population breeds throughout states within and around the Rocky Mountains and winters throughout parts of New Mexico, Arizona, and Mexico, over 90% of the RMP stopover in the San Luis Valley (SLV) in southcentral Colorado. Additionally, a smaller number of lesser sandhill cranes (A. c. canadensis) from the Midcontinent Population use the SLV during autumn and spring migration. During this time, sandhill cranes utilize riverine corridors, wetland complexes, wet meadows and pastures, and agricultural fields in the SLV on both private and public lands. A high proportion of their diet includes spilled barley and other grains leftover after harvest in autumn and before planting season the following spring. The Monte Vista National Wildlife Refuge (MVNWR) also provides supplemental barley for sandhill cranes in spring and manage water to provide emergent wetland and shallow water habitats for roosting and loafing. However, the SLV has experienced landscape changes that threaten important habitat for sandhill cranes, and most of these changes center around the availability of water. As a semi-arid and snowpack driven region, the hydrology of the SLV relies mostly on precipitation that comes from the surrounding mountains and on aquifers that provide irrigation water and recharge other water sources. Over the years, efforts to divert surface water and pump water from aquifers have led to overappropriation of water rights and reduced water availability. In addition, increasing temperatures and a changing climate are contributing to increasing water scarcity. These changes will likely influence the land use patterns, which could ultimately affect the supply of energy on the landscape and energetic demand of sandhill cranes. In turn, this could affect abundance and distribution. Understanding migration phenology, along with their bioenergetics and land use patterns while at a primary stopover area, are important for informing management on both public and private land and for estimating the carrying capacity of an area for migrant species. While the timing of RMP sandhill crane migration in the SLV has been documented previously, our first objective was to formally quantify their migration phenology in and out of the SLV and determine if there were weather or habitat covariates influencing their persistence probability. Migrant birds are thought to optimize migration timing and energy use by balancing the speed of migration with energetic consumption and expenditure. For example, migrating faster in the spring (i.e., time-minimization), and thus arriving earlier at the breeding grounds, may improve reproductive performance for some species. On the other hand, reducing the amount of energy (i.e., energy-minimization) used during migration may be preferred in autumn under reduced time constraints, so birds may take longer to migrate at this time of the year. Various factors will also influence how long birds remain at a stopover area, including weather patterns and habitat availability. As large birds, sandhill cranes may take advantage of various weather patterns, such as strong tailwinds or high wind speeds, to aid in flight and overall migration. These factors may reduce the probability that a sandhill crane will remain at a stopover if they incur a higher energetic cost. We examined the arrival probability and persistence probability of RMP sandhill cranes in the SLV using data across eight years from birds fitted with global system for mobile communication (GSM) platform transmitter terminal (PTT) tags or Global Positioning System (GPS) units. Using an open robust design mark-recapture model, we examined the influence of temperature change, barometric air pressure, tailwinds, crosswinds, wind speed, and surface water on the persistence probability of RMP sandhill cranes. Stopover duration was longer in autumn than in spring and had higher variability across years. Arrival probability to the SLV peaked on 13 October in autumn and 21 February in spring. Persistence probability declined around mid-December in autumn and mid-March in spring. We found that several weather covariates influenced persistence in both seasons. In autumn, sandhill cranes departed the SLV with higher tailwinds, lower crosswinds, and higher surface water availability. In spring, sandhill cranes departed the SLV with lower crosswinds and higher barometric air pressure at the surface and higher wind speeds at altitudes of about 3,000 m. The effect of wind speed was stronger later in the spring. Given the lower variability of arrival and persistence probability and shorter stopover duration in spring compared to autumn, we suspect that RMP sandhill cranes are using a time-minimization strategy during spring. However, given the use of supportive winds and weather conditions ideal for soaring, RMP sandhill cranes appear to be using strategies that save energy in both seasons. This study identified the optimal timing of water management and surveys for RMP sandhill cranes and confirms that weather influences their persistence. Understanding differences in migration patterns between seasons and the factors that influence persistence at stopover sites will also be important for anticipating phenological impacts from climate change and land use alterations. Next, we focused on how RMP sandhill cranes select habitat and use the SLV during their stopovers in autumn and spring. Sandhill cranes tend to show predictable movement patterns during migration in the SLV. They generally spend nights roosting in areas with shallow water (e.g., emergent wetlands, rivers, creeks, ponds) and leave the roosts around sunrise to forage primarily on grain fields. They spend midday loafing (i.e., resting and engaging in other behaviors) in various habitats, usually near or in water, and then return to feed one more time close to sunset before returning to the roost. This movement around a focal roosting point characterizes central place foragers. Given the risk of increasing water scarcity in the SLV and the potential for future landscape changes, quantifying the selection patterns of RMP sandhill cranes during their roosting, foraging, and loafing periods provides valuable information for habitat management. We used GSM/GPS data to examine the effects of water, sandbar, vegetation height, distance to the nearest grain field, landcover type, and ownership on roosting, loafing, and foraging habitat selection by RMP sandhill cranes. We found that sandhill cranes selected for areas with a high amount of water, relatively short vegetation (<5 m in autumn, <10 m in spring), close to grain fields (<5 km), and areas identified as open water for roosting. Loafing sandhill cranes also selected for areas with short vegetation and close to grain fields but that had less water and more sandbar than roosting areas and were identified as pastures or wetlands. While selection was higher for private land overall, we found evidence of avoidance of private lands and a stronger preference for public lands with increasing surface water for roosting in spring. For foraging areas, selection was highest for barley in both seasons, but triticale and other grains had relatively high selection in autumn. Our finding confirms the importance of providing roosting and loafing areas on both private and public lands close to foraging areas and provides evidence that roosting and loafing opportunities may be most limited on public lands in the SLV. We then examined foraging selection patterns more closely to define RMP sandhill crane distribution during migration and determine factors, in addition to habitat type, that affect selection for foraging areas. Flying is energetically expensive, so understanding some of the drivers of foraging preferences can inform management to aid in reducing the amount of energy required to find food. Greater sandhill cranes tend to forage within 2-5 km of their roost from the previous night. As food items in patches decline due to consumption and deterioration, sandhill cranes will move farther from their roost to forage. Other factors may motivate birds to switch patches. Tilling, for example, is a practice that takes place after harvest in many fields in the SLV and can also reduce seed availability. We sought to understand how tillage intensity in grain fields, along with crop type, distance to the nearest roost, and time, influence foraging selection by both greater sandhill cranes and lesser sandhill cranes. The same covariates were also used to examine their effects on the number of greater sandhill cranes. We completed roadside surveys to count greater and lesser sandhill cranes in autumn and spring and identify field-specific covariates. Lesser sandhill cranes were more concentrated in specific areas in the SLV, while greater sandhill cranes were more variable in their distribution. Selection in autumn was most influenced by an interaction between time and crop type for both subspecies, while spring selection was influenced by an interaction between crop type and roost distance. The probability of presence was highest on barley fields or other grains for both subspecies in mid-October and mid-March, but it declined as distance to the nearest roost increased for both subspecies. We only modeled covariates on abundance for greater sandhill cranes and found that an interaction between time and roost distance was the most influential model in autumn. The interaction between time and crop type most influenced abundance in spring. The effect of roost distance was negative early in the autumn season but became positive later in the season. Greater sandhill cranes also showed a higher abundance in other crop types in spring compared to autumn. We found that both greater and lesser sandhill cranes were more likely to be on fields with idle or low intensity tillage practices than those with high intensity tillage practices. Overall, our results suggested that sandhill cranes are variable in their use of the SLV for foraging and prefer to fly farther from roosts to their preferred forage type but may also switch to other crop types. While documenting phenology and selection patterns is useful for prioritizing areas for conservation and determining the appropriate habitat types to provide during migration, researchers and managers are lacking an understanding of how many sandhill cranes the SLV could theoretically support. Changing landscape and climate conditions in the SLV are contributing to increasing water scarcity, which may eventually reduce the amount of barley grown in the SLV or alter the juxtaposition of foraging and roosting areas. To understand how changes in barley tillage practices and amounts may influence RMP sandhill crane numbers in the SLV, our goals were to examine the influence of tillage intensity on barley availability, determine the energy demand of RMP sandhill cranes during autumn and spring, calculate the supply of energy available on the landscape from barley, and estimate current and potential carrying capacity under varying barley amounts. Idle fields (i.e., fields not tilled) had the greatest density of barley than fields that had low or high tillage intensity practices, and RMP sandhill cranes that used more tilled fields spent more time searching for forage. We also found an increase in lipid gain during spring migration, which increased the daily energetic expenditure (DEE) of RMP sandhill cranes during spring compared to autumn. Overall, we found that individual RMP sandhill cranes required between 458 to 566 kcal per day, which equated to 0.129 to 0.160 kg of barley per day, with a greater amount required during spring. The total energy demand required by the population for autumn was approximately 284.9 x 106 kcal (0.08 x 106 kg of barley), and this value increased to 435.4 x 106 kcal (0.1 x 106 kg of barley) for spring. The average energy supply was 5905.5 x 106 kcal (1.7 x 106 kg of barley) for early autumn and 1589.9 x 106 kcal (0.4 x 106 kg of barley) in late spring for the entire SLV. Overall, the supply of energy exceeded sandhill crane demand throughout both seasons. Based on bioenergetics models using the TRUEMET model, most scenarios also showed that energetic supply exceeded demand. Under all scenarios, barley declined by approximately 90% or more between early autumn to late spring, but supply was still greater than demand at the end of spring. While we made several assumptions using these models that could not be validated, we are confident that we provide evidence that there is currently enough barley in the SLV to support more sandhill cranes than the present population. Tillage intensity, particularly barley left idle in autumn and spring, appears to play a bigger role in barley availability than the presence of barley on public over private land. Overall, our findings provide information that can aid in practical management objectives in the face of climate and land use challenges and describe baseline information on how current conditions influence the energetics of the RMP. While the RMP appears to be relatively stable and increasing, several environmental changes in the SLV are likely to impact the distribution, timing of migration, and habitat selection patterns of the population. In turn, these factors will affect how sandhill cranes use and expend energy, which may lead to reduced reproduction or survival. Current objectives for the RMP include providing suitable habitat to support a population goal of 17,000 – 21,000 individuals. Our results indicate that habitat is sufficient for the current population and potentially a larger population. However, given the role of water in the movement and selection of sandhill cranes, increasing water scarcity is likely to temper the benefits of available forage over time, which may make meeting population objectives more challenging. Continued management of water and foraging resources on public and private lands are important, but our results also emphasize the need to integrate habitat management on both ownership types to ensure adequate resources are available during migration.
Keywords: bioenergetics; migration; sandhill crane; habitat selection; agriculture; San Luis Valley